2022
DOI: 10.3389/fpsyg.2022.891532
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences, Mindfulness, and Grit in College Students in China

Abstract: This study investigated the effect of ACEs and COVID-19 on grit and whether this effect is mediated by mindfulness. Although current scholarship has found that adverse childhood experiences (ACEs) have harmful consequences to individuals across the life span, less is known about the relationship between ACEs and grit. Grit is predictive of educational success and subjective wellbeing. A cross-sectional online survey administered to junior and senior students from 12 universities spread across China was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Duckworth et al 28 defined grit as people’s consistency of interests and perseverance of effort, i.e., the passion and tenacity in pursuing certain goals. Supporting the mindfulness-to-meaning theory [× 20] and self-determination theory 27 , recent studies suggested that mindfulness is associated with grit 29 31 . For instance, mindfulness facets including acting with awareness and non-judging were found to predict grit longitudinally 31 .…”
Section: Introductionmentioning
confidence: 95%
“…Duckworth et al 28 defined grit as people’s consistency of interests and perseverance of effort, i.e., the passion and tenacity in pursuing certain goals. Supporting the mindfulness-to-meaning theory [× 20] and self-determination theory 27 , recent studies suggested that mindfulness is associated with grit 29 31 . For instance, mindfulness facets including acting with awareness and non-judging were found to predict grit longitudinally 31 .…”
Section: Introductionmentioning
confidence: 95%